A Novel Thermally Reversible Soluble‐Insoluble Conjugated Polymer with Semi‐Fluorinated Alkyl Chains: Enhanced Transistor Performance by Fluorophobic Self‐Organization and Orthogonal Hydrophobic Patterning. (29th August 2013) - Jeong, Hyung‐Gu; Lim, Bogyu; Khim, Dongyoon; Han, Mingu; Lee, Jaewon; Kim, Juhwan; Yun, Jin‐Mun; Cho, Kilwon; Park, Ji‐Woong; Kim, Dong‐Yu
<x xml:space="preserve">Abstract</x> SFA‐PQT exhibits self‐assembly via a fluorophobic effect in a non‐fluorous solvent, which leads to an enhanced electrical performance. Ambipolar transistors and inverters with p‐ and n‐ type bilayers are enabled by the unique thermally reversible soluble‐insoluble properties of SFA‐PQT. More importantly, the hydrophobicity of SFA‐PQT facilitates orthogonal hydrophobic patterning and a patterned inverter exhibits low voltage dissipation, a narrow transition zone, a high gain value, and negligible hysteresis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>